2010
DOI: 10.1111/j.1471-0307.2010.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thiocyanate and hydrogen peroxide on the keeping quality of ovine, bovine and caprine raw milk

Abstract: The preservation of raw ovine, bovine and caprine milks by the activation of their natural lactoperoxidase (LP) systems was investigated. The LP system of the samples was activated by adding different amounts of sodium thiocyanate and sodium percarbonate to give three different concentrations of thiocyanate and hydrogen peroxide: 7, 14 and 28 mg/L and 15, 30 and 60 mg/L, respectively. Each type of raw milk, ovine, bovine and caprine, was analysed after being treated as follows: Control (C), LP inactivated (T0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
4
7
0
Order By: Relevance
“…However, lower pH values were observed for milk stored at 4 °C during 48, 72 and 96 h. This result was in agreement with previous researchers reporting a decrease in the pH value from 6.82 ± 0.06 to 6.75 ± 0.11 and 6.61 ± 0.26, after a storage time at 4 °C for 24 h, 3 and 4 days, respectively (Ruas‐Madiedo et al. 1998; Boularès et al. 2011b).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, lower pH values were observed for milk stored at 4 °C during 48, 72 and 96 h. This result was in agreement with previous researchers reporting a decrease in the pH value from 6.82 ± 0.06 to 6.75 ± 0.11 and 6.61 ± 0.26, after a storage time at 4 °C for 24 h, 3 and 4 days, respectively (Ruas‐Madiedo et al. 1998; Boularès et al. 2011b).…”
Section: Resultssupporting
confidence: 92%
“…In general, the physicochemical composition of milk samples showed average values similar to those described by previous findings during the refrigeration of milk at 4 °C for different times (Ruas‐Madiedo et al. 1998; Boularès et al. 2011b).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Proteolysis in UHT milk samples may be due to plasmin and/or bacterial proteinases and/or SCC elastase and catehepsin G (Bastian and Brown, 1996; Le Roux et al, 2003), which depends on the microbiological quality of milk samples. Thus, activation of LPS in refrigerated raw milk improves its hygienic quality (Boulares et al, 2011) and reduces its concentration of extracellular bacterial proteinases, compared with control raw milk.…”
Section: Resultsmentioning
confidence: 99%
“…The reactions inhibit growth of both Gram negative (e.g., Escherichia coli O157:H7) and Gram positive bacteria (e.g., Listeria monocytogenes), thus making the LPSys potentially useful in improving food safety (Elliot et al, 2004;El-Shenawy, Garcia, & Marth, 1990;Marshall & Reiter, 1980). Although investigators have demonstrated the effect of the LPSys in milk (Boulares, Mankai, & Hassouna, 2011;Seifu, 2007;Seifu, Buys, & Donkin, 2005), application in other food systems is limited. For example, application of the LPSys in beef cubes significantly reduced the number of microorganisms including L. monocytogenes after 7 d of incubation at 12 C (Elliot et al, 2004).…”
Section: Introductionmentioning
confidence: 97%